2016
DOI: 10.1177/0883073816653782
|View full text |Cite
|
Sign up to set email alerts
|

Medical Comorbidity of Attention-Deficit/Hyperactivity Disorder in US Adolescents

Abstract: Understanding patterns of medical comorbidity in attention-deficit/hyperactivity disorder (ADHD) may lead to better treatment of affected individuals as well as aid in etiologic study of disease. This article provides the first systematic evaluation on the medical comorbidity of ADHD in a nationally representative sample (National Comorbidity Replication Survey-Adolescent Supplement; N = 6483) using formal diagnostic criteria. Survey-weighted odds ratios adjusted for demographics, additional medical, and menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 74 publications
5
16
0
1
Order By: Relevance
“…To some extent, these findings echo relations observed in the general population, as children without ASD also tend to display increased GI concerns in the context of both externalizing disorders such as ADHD ( 29 ) as well as internalizing symptoms such as anxiety and depression ( 30 ). However, interactions between psychiatric and GI symptoms are particularly pertinent in ASD, as the core symptoms of ASD appear to affect these associations.…”
Section: Introductionsupporting
confidence: 59%
“…To some extent, these findings echo relations observed in the general population, as children without ASD also tend to display increased GI concerns in the context of both externalizing disorders such as ADHD ( 29 ) as well as internalizing symptoms such as anxiety and depression ( 30 ). However, interactions between psychiatric and GI symptoms are particularly pertinent in ASD, as the core symptoms of ASD appear to affect these associations.…”
Section: Introductionsupporting
confidence: 59%
“…ADHD can cause considerable disability and impaired quality of life 2 . Furthermore, children with ADHD also suffer from a high prevalence of co-occurring medical and psychiatric conditions such as depressive disorder, anxiety disorder, restless leg syndrome, enuresis, and serious stomach problems 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Jameson et al reported data from the National Comorbidity Survey‐Adolescent Supplement, which gathered data from a “parent self‐administered” questionnaire, with migraine identified via self‐report of “severe headaches or migraines.” Logistic regression models (adjusted for sex, age, ethnicity, and parent education) revealed an odds ratio of 1.46 (95%CI 1.07‐1.98) for “severe headaches/migraines” in ADHD. However, once the model was further adjusted for other medical disorders, the association was no longer significant, with an adjusted OR of 1.22 (0.90‐1.65).…”
Section: Attention‐deficit/hyperactivity Disordermentioning
confidence: 99%